Unveiling the role of EVs in anaerobic parasitic protozoa. (May 2021) - Sabatke, Bruna; Gavinho, Bruno; Coceres, Veronica; de Miguel, Natalia; Ramirez, Marcel I.
Highlights: Different anaerobic protozoans release extracellular vesicles (EVs). Protozoa produce EVs that modulate host-parasite interaction. EVs contribute to pathogenesis of diseases caused by anaerobic. Anaerobic EVs analysis by proteomics help to understand communication intercellular. Abstract: The anaerobic or microaerophilic protozoan parasites such as the enteric human pathogens Entamoeba histolytica, Giardia intestinalis, Cryptosporidium parvum, Blastocystis hominis and urogenital tract parasites Trichomonas vaginalis are able to survival in an environment with oxygen deprivation. Despite living in hostile environments these pathogens adopted different strategies to survive within the hosts. Among them, the release of extracellular vesicles (EVs) has become an active endeavor in the study of pathogenesis for these parasites. EVs are heterogenous, membrane-limited structures that have played important roles in cellular communication, transferring information through cargo and modulating the immune system of the host. In this review, we described several aspects of the recently characterized EVs of the anaerobic protozoa, including their role in adhesion, modulation of the immune response and omics analysis to understand the potential of these EVs in the pathogenesis of these diseases caused by anaerobic parasites.